An exploration of pharmacists' learning in practice - Gifford, Alison Jane (2008)
Informal learning is a major factor influencing the professional development and practices of health professionals (Eraut, 1994). This thesis is an in-depth exploration of how this process occurs in pharmacy and involves a detailed study of practising pharmacists. The learning approach of these individuals is explored in relation to the variety of working situations in which they practise and the prevailing climate in relation to professional learning and development within the National Health Service (NHS). This study therefore adds to an understanding of the way in which informal learning shapes the practice of pharmacists and as such it has considerable implications for both future policy and practice.